KDYMM Regent of Pahang, Tengku Hassanal Ibrahim Alam Shah proclaimed as UMPSA's Pro-Chancellor - Safriza, Baharuddin (UMPSA, 2023)
GAMBANG, 21 October 2023 - The Yang di-Pertuan Agong, Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Al-Marhum Sultan Haji Ahmad Shah Al-Musta’in Billah consented to the proclamation of the Regent of Pahang Tengku Mahkota Tengku Hassanal Ibrahim Alam Shah Ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah as the Pro-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) today.